Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/bfj-08-2021-0905
|View full text |Cite
|
Sign up to set email alerts
|

Exploring agricultural entrepreneurship and new technologies: academic and practitioners' views

Abstract: PurposeThis paper investigates the relationship between agricultural entrepreneurship (AE) and new technologies using academic and practitioners' perspectives to understand how new technologies such as artificial intelligence (AI), machine learning and augmented reality can promote agri-businesses.Design/methodology/approachThe paper adopts a content and thematic analysis of 325 academic sources extracted from the Scopus database and 683 patents retrieved from the European Patent Office (EPO) dataset. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Rethinking the agri-food system, and changing overall consumer habits in relation to food is crucial for achieving macro-level social, economic and environmental goals (Arrieta and Gonz alez, 2018;Alexander et al, 2019;Lu et al, 2019). Despite numerous recent innovations that have lessened their environmental impact (Adams et al, 2016;Secinaro et al, 2021), the meat, dairy and seafood industries still represent a major environmental threat (Erb et al, 2016;Notarnicola et al, 2017;Van Mierlo et al, 2017). Approximately 70% of agricultural land How do vegfriendly restaurateurs 'crop up'?…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Rethinking the agri-food system, and changing overall consumer habits in relation to food is crucial for achieving macro-level social, economic and environmental goals (Arrieta and Gonz alez, 2018;Alexander et al, 2019;Lu et al, 2019). Despite numerous recent innovations that have lessened their environmental impact (Adams et al, 2016;Secinaro et al, 2021), the meat, dairy and seafood industries still represent a major environmental threat (Erb et al, 2016;Notarnicola et al, 2017;Van Mierlo et al, 2017). Approximately 70% of agricultural land How do vegfriendly restaurateurs 'crop up'?…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite numerous recent innovations that have lessened their environmental impact (Adams et al. , 2016; Secinaro et al. , 2021), the meat, dairy and seafood industries still represent a major environmental threat (Erb et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2020). Agricultural computerisation allows energy saving and sustainability increases, whereas smart drone systems and automatic mobile robots are used to monitor the agricultural produce and to carry field crops (Secinaro et al. , 2022; Trivelli et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another complementary cluster includes technologies supporting decision making such as artificial intelligence and data mining. In relation to agricultural entrepreneurship, Secinaro et al (2022) identified macro-topics and themes referring to the value created through new technologies for agri-food entrepreneurs. However, moving from precision agriculture, extant research has scarcely investigated Industry 4.0 applications across other activities of the agri-food supply chain (Lezoche et al, 2020) and extant works are mainly theoretical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation